Conformity Motivation as a Disruptor of Intergenerational Influence within Australia - Osborne, Delane; Marchegiani, Chris (Australian and New Zealand Marketing Academy, 2012)
This paper adds to the existing body of knowledge on intergenerational influence by exploring the effects of peer conformity in an Australian context. This is in line with the Marketing Science Institute’s research priority to engage in research that enables greater understanding of consumer behavior. In this study the Attention to Social Comparison Index is utilized as a measure of peer conformity with individuals classified by their index score. This score is then regressed against intergenerational influence with results providing empirical evidence that desire to conform to peer reference groups can act as a disrupter of intergenerational influence. This indicates that within Australia, individuals who are more conscious of the opinions and attitudes of others are more susceptible to peer influence than familial influence for highly visible consumption and prestige behaviours. This finding bears managerial significance as products within this classification should be marketed accordingly.